(untitled) (Al-Academy, 2023)
Reduction has been linked visually in art since man began making functional and aesthetic forms, and this beginning can be identified with cave paintings. Reduction is one of the clearest indications of intellectual presence in aesthetic experience. Modernism was greatly supported by the great transformations that the intellectual movement witnessed in the world in general and in Europe in particular. There, and their transfer of European artistic experiences, and the reflection of this influence in their aesthetic sculptures, and for this reason the researchers find that the study of the aesthetic references of the reductive forms in the Iraqi sculptural experience represents a great importance in the study of the history of contemporary sculpture, to consider the concept of reduction and its performance applications, so the research includes four chapters The first chapter included the methodological framework for the research, and in it we reviewed the research problem, as we explained in it the plastic art’s dealings in general with the concept of reduction, and then the applications of reduction in the art of European and Iraqi sculpture, starting from this question: What are the references for selection in contemporary Iraqi sculpture? Then we presented the importance of the research and its aim in identifying the working mechanisms of the concept of shorthand and its references in contemporary Iraqi sculpture, and the limits of research between (2003-2023), and we showed a number of definitions of shorthand linguistically, idiomatically and procedurally.Then, in the second chapter marked by the theoretical framework of the research: we presented three topics, the first of which was devoted to the concept of shorthand and its performance applications in the arts of ancient civilizations. The second topic was devoted to the study of reductionism in the arts of European modernity, and in the third topic, we dealt with reductionism in contemporary Iraqi sculpture, and then presented the theoretical framework indicators.In the third chapter tagged: the procedural framework of the research: we presented the research community, which included all the Iraqi artists who worked in the shorthand format in their sculptural works within the limits of the research, and we set a number of conditions for choosing the research sample, and it was chosen in an intentional way, and it included four samples, and we also used the observation tool to collect The research sample information, and the analysis was done according to the descriptive analytical method.The researchers reached a number of results, including: that the act of reduction is a dominant and distinctive feature in the outputs of contemporary Iraqi sculpture, which depends on simplification, pruning and deletion, and also achieved by symbolic abbreviations in the artwork and the concentration and intensification of the significance, as it appeared that the contemporary Iraqi sculptor was influenced by the European artistic schools and trends that dominated On the global artistic act in the twentieth century, and what followed within the precursors of preoccupation with the arts of modernity and beyond, in addition to being affected by the cultural depth of the civilization of the Mesopotamia Valley, just as reductionism achieved for the sculptor proof of his self and personal style, then we presented recommendations and proposals. Then we included proven sources, references and appendices.